Constraints on potential enzyme activities in thermokarst bogs: Implications for the carbon balance of peatlands following thaw. (10th July 2021) - Heffernan, Liam; Jassey, Vincent E. J.; Frederickson, Maya; MacKenzie, M. Derek; Olefeldt, David
Abstract: Northern peatlands store a globally significant amount of soil organic carbon, much of it found in rapidly thawing permafrost. Permafrost thaw in peatlands often leads to the development and expansion of thermokarst bogs, where microbial activity will determine the stability of the carbon storage and the release of greenhouse gases. In this study, we compared potential enzyme activities between young (thawed ~30 years ago) and mature (~200 years) thermokarst bogs, for both shallow and deep peat layers. We found very low potential enzyme activities in deep peat layers, with no differences between the young and mature bogs. Peat quality at depth was found to be highly humified (FTIR analysis) in both the young and mature bogs. This suggests that deep, old peat was largely stable following permafrost thaw, without a rapid pulse of decomposition during the young bog stage. For near‐surface peat, we found significantly higher potential enzyme activities in the young bog than in the mature—associated with differences in peat quality derived from different Sphagnum species. A laboratory incubation of near‐surface peat showed that differences in potential enzyme activity were primarily influenced by peat type rather than oxygen availability. This suggested that the young bog can have higher rates of near‐surface decomposition despite being substantially wetter than the mature bog. Overall, our study shows that peat properties are the dominant constraint on potential enzyme activity and that peatland site development (successional pathways and permafrost history) through its influence on peat type and chemistry is likely to determine peat decomposition following permafrost thaw. Abstract : Potential enzyme activities suggest that deep, previously frozen peat was relatively stable in the initial decades and up to ~200 years following permafrost thaw. We found significantly higher potential enzyme activities in peat nearer the surface, particularly in the initial decades following thaw. This study shows that the influence of site development on peat type and chemistry are the main constraints on enzyme activity in peatlands following permafrost thaw.